The concise encyclopedia of the ethics of new technologies - Chadwick, Ruth F. (Academic Press, 2001)
"The ethical assessment of new technologies raises two principal concerns: the need to develop effective policies and legislation, and the reconsideration of the ethical frameworks in which these policies and laws are developed. The importance of rapid, accurate examinations of tensions between Philosophy and Law and the relationship between philosophical principles and empirical data has never been greater. The Concise Encyclopedia of Ethics of New Technologies includes 23 articles previously published in the highly-acclaimed Encyclopedia of Applied Ethics, nine updated articles, and five new articles, commissioned especially for this volume. Over half of the previously published articles include updated facts and bibliographic citations. Authors of genetics articles have updated their works to include the most recent developments and publications. New articles include: "Cloning," "Geneticization," "Health Technology Assessment," "Intrinsic and Instrumental Value," and "Novel Foods."--Publisher description (LoC)